Genome-wide screen reveals cellular functions that counteract rifampicin lethality in Escherichia coli - Yu Wang; Han Fu; Xiao-Jie Shi; Guo-Ping Zhao; Liang-Dong Lyu (Microbiology Spectrum, 2024)
ABSTRACT The antibacterial activity of rifamycins specifically relies on the inhibition of transcription by directly binding to the β-subunit of bacterial DNA-dependent RNA polymerase (RNAP). However, its killing efficacy is substantially diminished in most gram-negative bacteria. To systematically reveal the cellular functions that counteract rifamycin-mediated killing in the gram-negative model organism Escherichia coli, we performed a genome-wide Tn5 transposon-mediated screen to identify mutants with altered susceptibility to rifampicin. Combined with targeted gene knockouts, our results showed that the β-barrel assembly machinery plays a crucial role in restricting rifampicin from entering the cell, whereas mutants deficient in other cellular permeability barriers, such as lipopolysaccharide and enterobacterial common antigen, had no such effect. At bactericidal concentrations, the killing efficacy of rifampicin was strongly influenced by cellular functions, including iron acquisition, DNA repair, aerobic respiration, and carbon metabolism. Although iron acquisition de facto has a strong impact or dependence on cellular redox, our results suggest that their effects on rifampicin efficacy do not rely on hydroxyl radical formation. We provide evidence that maintenance of DNA replication and transcription-coupled nucleotide excision repair protects E. coli cells against rifampicin killing. Moreover, our results showed that sustained aerobic respiration and carbon catabolism diminish rifampicin’s killing efficacy, and this effect relies on the inhibition of transcription but not on translation. These findings suggest that the killing efficacy of rifamycins is largely determined by cellular responses upon the inhibition of RNAP and may expand our knowledge of the action mechanisms of rifamycins. IMPORTANCE Rifamycins are a group of antibiotics with a wide antibacterial spectrum. Although the binding target of rifamycin has been well characterized, the mechanisms underlying the discrepant killing efficacy between gram-negative and gram-positive bacteria remain poorly understood. Using a high-throughput screen combined with targeted gene knockouts in the gram-negative model organism Escherichia coli, we established that rifampicin efficacy is strongly dependent on several cellular pathways, including iron acquisition, DNA repair, aerobic respiration, and carbon metabolism. In addition, we provide evidence that these pathways modulate rifampicin efficacy in a manner distinct from redox-related killing. Our findings provide insights into the mechanism of rifamycin efficacy and may aid in the development of new antimicrobial adjuvants.